(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
In our stories, we carry the concept of voice in various forms. In the context of contact the Indigenous ‘voice’ is one ever-present and evolving. It is omnipresent, laying down new foundations for the ‘voice’ through to new generations. It is the representation of an entire culture. It is not a natural language or the voice of academia. It is as ancient as its land and lies at the heart of its peoples. It is a cultural voice. It is the voice of the dreaming. It is the voice of resistance. It is the voice of self-determination.